New ß-galactosidase producers with potential for prebiotic synthesis - Silvério, Sara Isabel Cruz (2018)
ß-galactosidases (EC 3.2.1.23) are interesting enzymes with potential application in the pharmaceutical and food industry. In this work, a screening study was carried out to identify new fungal sources of -galactosidase. A total of 50 fungi were evaluated using a chromogenic test performed in agar plates. The most promising microorganisms were validated as effective -galactosidase producers under submerged fermentation conditions. The crude -galactosidases were characterized regarding their optimal pH (3.0-5.5) and temperature (45-65 °C). All enzymes showed ability to synthesize lactose-based prebiotics, namely lactulose (maximal yield 3.3%) and a galacto-oligosaccharide (GOS) (maximal yield 20%). Additionally, some enzymatic extracts with fructosyltransferase activity allowed to produce other type of prebiotics, namely fructo-oligosaccharides (FOS). This work, reports for the first time the simultaneous synthesis of different mixtures of GOS (2-15% yield and 0.07-0.5 g/L·h-1 productivity) and FOS (4-30% yield and 0.1-1 g/L·h-1 productivity) by crude extracts exhibiting dual enzymatic activity.